Perbedaan Prestasi Belajar Siswa Kelas VIII SMPN 1 KEDIRI dengan Penerapan Model Pembelajaran Kooperatif Tipe Student Team Achievement Division (STAS) dan Numbered Head Together (NHT) Pada Materi Sistim Koordinat Kartesius Tahun Pelajaran 2018/2019 - Hidayat, Rahman; Sutarto, Sutarto; Hastuti, Intan Dwi (PeDaPAUD: Jurnal Pendidikan Dasar dan PAUD, 2022)
This study aims to determine whether there are differences in maths learning achievement between classes taught by cooperative learning model Student Team Achievement Division (STAD) type and class taught by cooperative learning type Numbered Head Together (NHT) in material sistim coordinat cartesius class VIII SMP Negeri 1 Kediri 2018/2019 school year. Data collection techniques in this study are test techniques with instruments in the form of learning achievement test, learning implementation observasion sheets and learning implementation. Data analysis techniques use descriptive statistics. Hypothesis test of students' final ability (posstest) with t-test of two parties at a significance level of 5% resulted in tcount